THE PROBLEM OF DETERMINING THE COMPETENCES OF TEACHER TECHNOLOGIES TO MAKE EFFECTIVE PEDAGOGICAL ACTIVITY - Procko, Kh.V. (Pedagogy of Higher and Secondary Education, 2009)
In article the definition problem competence teachers of technologies with which help probably to provide not only the international recognition of diplomas, and a recognition of their professional suitability has been opened.